Newcomer proactive behavior and adjustment among school teachers in northern province of sri lanka - Kowsikka, F. M. J. J.; James, R. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
Newcomers make the transition from being organizational outsiders to being insiders. During this process employees learn organizational environment and intergrade themselves into that environment. Previous studies much investigated the role of organization in the socialization/adjustment process, but less investigated the individual’s role in that process. This study aimed to investigate the role of newcomers’ proactive behavior in the adjustment process among 98 school teachers in Northern Province of Sri Lanka. This study employed PLS-SEM with SmpartPLS to test proposed hypotheses. This study found that newcomers’ engagement in proactive behaviours such as feedback seeking, information seeking, relationship building and positive framing positively influence their adjustment (social integration). These findings suggest that individuals need to be proactive and engage in positive framing, information seeking, relationship building, and feedback seeking to become acceptable members of the organization and be successful in their career. Also organizations need to encourage newcomers to engage in proactive behavior through maintaining appropriate organizational culture to get better outcomes from their employees. Further, this study contributes to the literature by investigating the influence of proactive behaviour in the socialization process among school teachers which is the population unnoticed in the socialization literature.
Keywords: Socialization; Adjustment; Newcomer; Proactive Behaviour; Social Integration; School Teachers